Desired emotions across cultures A value-based account. [article]. - Tamir, Maya
Values reflect how people want to experience the world; emotions reflect how people actually experience the world. Therefore, we propose that across cultures people desire emotions that are consistent with their values. Whereas prior research focused on the desirability of specific affective states or 1 or 2 target emotions, we offer a broader account of desired emotions. After reporting initial evidence for the potential causal effects of values on desired emotions in a preliminary study (N = 200), we tested the predictions of our proposed model in 8 samples (N = 2,328) from distinct world cultural regions. Across cultural samples, we found that people who endorsed values of self-transcendence (e.g., benevolence) wanted to feel more empathy and compassion, people who endorsed values of self-enhancement (e.g., power) wanted to feel more anger and pride, people who endorsed values of openness to change (e.g., self-direction) wanted to feel more interest and excitement, and people who endorsed values of conservation (e.g., tradition) wanted to feel more calmness and less fear. These patterns were independent of differences in emotional experience. We discuss the implications of our value-based account of desired emotions for understanding emotion regulation, culture, and other individual differences. -- (from the authors)